2013
DOI: 10.1366/13-07040
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Far-Infrared Spectroscopic Studies of Hydrogen Bonding in Formic Acid

Abstract: Simple molecules such as HCOOH, or formic acid, are suggested to have played important roles in planetary physics due to their possibility for high pressure and temperature chemistry under impact conditions. In this study, we have investigated the effect of pressure (up to 50 GPa) on H-bonding and reactivity of formic acid using synchrotron far infrared spectroscopy. Based on the pressure-induced changes to H-bond ν(O-H···O) stretching and γ(O-H···O) deformations, we observe significant reorganization of H-bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…We observed two instances of complexation formation via C−C pair interactions ("hot" trajectory only), 62 instances via C−hydroxyl O interactions (43 for the "cold" and 19 for the "hot"), and 78 instances via C−carbonyl O interactions (49 for the "cold" and 29 for the "hot"). These interactions are similar to those seen in experimental 2,38 and theoretical studies 2 of formic acid under high pressure static compression, where both papers observed hydrogen bond symmetrization at pressures of ∼20 GPa and polymerization occurring at ∼40 GPa, although those studies were performed at room temperature. As stated earlier, only 26 molecules displayed CO or CH scission reactions (for both the "cold" and "hot" trajectories), while there were 142 instances in which complexes were formed.…”
Section: Resultssupporting
confidence: 84%
“…We observed two instances of complexation formation via C−C pair interactions ("hot" trajectory only), 62 instances via C−hydroxyl O interactions (43 for the "cold" and 19 for the "hot"), and 78 instances via C−carbonyl O interactions (49 for the "cold" and 29 for the "hot"). These interactions are similar to those seen in experimental 2,38 and theoretical studies 2 of formic acid under high pressure static compression, where both papers observed hydrogen bond symmetrization at pressures of ∼20 GPa and polymerization occurring at ∼40 GPa, although those studies were performed at room temperature. As stated earlier, only 26 molecules displayed CO or CH scission reactions (for both the "cold" and "hot" trajectories), while there were 142 instances in which complexes were formed.…”
Section: Resultssupporting
confidence: 84%
“…17 At very high pressures, above 35 GPa, a band just over 300 cm −1 is attributed to amorphous formic acid. 2,78 The aerosol band position at 242 cm −1 is more similar to that of formic acid "glass" (249 cm −1 ) 33 and to that of the cyclic dimer at 251 cm −1 (see Figure 1). Noting the similarity of the broad far-IR band of amorphous formic acid to this dimer feature, Iopollo et al 2 assigned it to a rocking mode of the cyclic dimer.…”
Section: Resultsmentioning
confidence: 70%
“…One previous study displays a spectrum attributed to amorphous formic acid: it is somewhat noisy and limited to the region below 250 cm –1 but has a band with position given as 227 cm –1 . ,, Another study cites a band at ∼235 cm –1 for formic acid deposited at 77 K prior to annealing . At very high pressures, above 35 GPa, a band just over 300 cm –1 is attributed to amorphous formic acid. , The aerosol band position at 242 cm –1 is more similar to that of formic acid “glass” (249 cm –1 ) and to that of the cyclic dimer at 251 cm –1 (see Figure ). Noting the similarity of the broad far-IR band of amorphous formic acid to this dimer feature, Iopollo et al assigned it to a rocking mode of the cyclic dimer.…”
Section: Results and Discussionmentioning
confidence: 97%
“…2, the medium intensity IR modes 44,46 can be observed near 227 cm −1 and 480 cm −1 in ref. 38 above 20 GPa.…”
mentioning
confidence: 98%
“…This evolution explains the soft mode behavior of the OH-stretching IR mode reported up to 12.2 GPa. 2 To the best of our knowledge, the mid-IR absorption studies of FA have not been conducted at higher pressures, owing to absorption saturation, 38 which evaded crucial molecular information under high pressures. Here, we have measured the mid-IR reflectance of FA above 12 GPa, which systematically follow the reported data up to this pressure, 2 presented in Fig.…”
mentioning
confidence: 99%